(3Ojf GdOQhRs
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdMGce GdefGf GdMeO dehdGfG eXgQ GdcdjGJ EYdehG eYGTQ GdehMOjf dehdGfG GdMGce ahVYJ gPG GdcJGH hgh GdLRA GdChd ef GdSHYI GLRGA JTJed Ydi aQGFV aQVgG ehdGfG SHMGfg s
(3BNQgG (B:s
(3jfJgi HChd GdQSGdI GdehSheI HGdEjbGX hGdHTGQI dCgd GdZadI hGd GdMb HGdWgGQI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdCeQjcjI ai HjQhJ s
Keywords: (3abg GdePGgH GdCNQis